WHAT IS THE ANSOFF MATRIX AND HOW TO UTILIZE IT IN BUSINESS ANALYSIS? - Pahlefy, Muhamad Reza; Putri, Tasya Amanda (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
In the dynamic era of globalization and competitive markets, businesses face multifaceted challenges in achieving sustainable growth and adaptability. The Ansoff Matrix, developed by Igor Ansoff in 1957, serves as a pivotal strategic framework for identifying growth opportunities by focusing on product and market dimensions. This study explores the theoretical underpinnings and practical applications of the Ansoff Matrix, providing insights into its four strategic options: market penetration, market development, product development, and diversification. Utilizing a structured literature review methodology, this research critically examines the matrix's relevance, benefits, and limitations in contemporary business scenarios. Findings reveal that while the matrix offers simplicity and strategic clarity, its application demands integration with dynamic market analysis and agility. This study underscores the matrix's value as a decision-making tool for aligning growth strategies with organizational capabilities and market demands, ensuring competitive advantage and long-term success.